Multiculturalism still matters in education and society : responding to changing times - Obiakor, Festus E. (Emerald Publishing Limited : Information Age Publishing, 2021)
"Today, we live in changing times and how we respond to these changes creates some uneasiness in our daily lives. For example, these changes reflect demographic shifts in power and paradigm in the United States, rather than assume that our problems are insurmountable, multiculturalism still matters in education and society: responding to changing times urges us to collaborate, consult, and cooperate for our common good. This book also rightly emphasizes that multiculturalism will always matter in whatever we do in our complex world. In addition, it challenges us to continue to see differences as strengths that must be valued in dealing with our students, educational professionals, leaders, and communities. Finally, this book inspires us to expand our discourses, create avenues for hearty conversations, look for ways to hear and make invisible voices visible, and help culturally and linguistically diverse (cld) and vulnerable populations to maximize their fullest potential"-- Provided by publisher.
Keywords: Multicultural education -- United States.; Minorities -- Education -- United States.; Multiculturalism -- United States.; Social change -- United States.; Education -- Multicultural Education.; Educational strategies and policy: inclusion.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books